“Why Industrial Textile to Right Choice for Investment” (Analisis Laporan Keuangan PT. Eratex Djaja dan PT. Polychem Indonesia Tahun 2013-2017) - Fitrisia Fitrisia; Irma Suryani Indra; Silmi Silmi (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Investors need analytical assistance to invest and related to what capital will be invested in the industry and what benefits will be obtained. Therefore, industry analysis can help investors make choices. One good industry choice for investing is the textile industry, because the needs of textile goods are everyone's basic needs for making clothes and other items such as dolls, blankets, bags and wallets. This makes the textile industry needs to be a consideration for investing. The development of the textile industry in Indonesia is growing rapidly, because there are currently 43 companies engaged in the textile sector that have gone public. This shows that the textile industry is very good for investment analysis. The analysis uses industry financial data for five years, from 2013 to 2017.